2006
DOI: 10.2337/db06-0191
|View full text |Cite
|
Sign up to set email alerts
|

New Polymorphism of ENPP1 (PC-1) Is Associated With Increased Risk of Type 2 Diabetes Among Obese Individuals

Abstract: The K121Q polymorphism in ectonucleotide pyrophosphatase/phosphodiesterase 1 (ENPP1) is associated with type 2 diabetes and obesity. The possibility of other ENPP1 polymorphisms influencing these phenotypes has received little attention. Our aim was to examine the associations of tagging single nucleotide polymorphisms (SNPs) and haplotypes of the linkage disequilibrium (LD) block containing K121Q polymorphism with type 2 diabetes in a Polish population, controlling for any effect of obesity. We genotyped 426 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
38
1
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(50 citation statements)
references
References 21 publications
(28 reference statements)
7
38
1
2
Order By: Relevance
“…Indeed, recently a meta-analysis and a meta-regression have shown that the deleterious effect of the PPARG P12/P12 genotype on diabetes risk is augmented in studies where control subjects were leaner (25), thus suggesting that this may be a common phenomenon characterizing the effect of insulin resistance genes on the risk of type 2 diabetes. Since our meta-regression of ENPP1 K121Q is limited by the use of population BMI averages rather than individual measures, we cannot verify whether our present finding is related to the reported interaction between the K121Q polymorphism and BMI in modulating the risk of type 2 diabetes (15,21,22).…”
Section: Enpp1 K121q Meta-analysis In Type 2 Diabetescontrasting
confidence: 49%
“…Indeed, recently a meta-analysis and a meta-regression have shown that the deleterious effect of the PPARG P12/P12 genotype on diabetes risk is augmented in studies where control subjects were leaner (25), thus suggesting that this may be a common phenomenon characterizing the effect of insulin resistance genes on the risk of type 2 diabetes. Since our meta-regression of ENPP1 K121Q is limited by the use of population BMI averages rather than individual measures, we cannot verify whether our present finding is related to the reported interaction between the K121Q polymorphism and BMI in modulating the risk of type 2 diabetes (15,21,22).…”
Section: Enpp1 K121q Meta-analysis In Type 2 Diabetescontrasting
confidence: 49%
“…Having established the association between ENPP1 K121Q and hyperglycemia, we explored the interaction between K121Q and BMI because of preliminary evidence that the effect of the Q allele on glycemic traits is mediated by an increase in adiposity (3,5,7,13,30) and suggestions that this variant may also contribute to obesity traits (5,6,(31)(32)(33). Although we observed no association of ENPP1 K121Q with BMI or waist circumference, our interaction analysis supports the observation that a higher BMI strengthens the association of this particular polymorphism with elevated insulin resistance and glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes 57: [1971][1972][1973][1974][1975][1976][1977]2008 E ctonucleotide pyrophosphatase phosphodiesterase 1 (ENPP1), also known as plasma cell membrane glycoprotein 1 (PC-1), is a transmembrane glycoprotein that down-regulates insulin signaling in cells by inhibiting the tyrosine kinase activity of the insulin receptor, perhaps by interaction with its ␣-subunit (1). Within the coding region of ENPP1, a K3 Q missense single nucleotide polymorphism (SNP) at position 121 (K121Q; rs1044498) has been previously associated with insulin resistance and related abnormalities in some studies (2)(3)(4)(5)(6)(7). The molecular mechanism thought to be responsible for the role of the Q121 variant is a "gain of function" of the ENPP1 protein inhibitory activity on the insulin receptor (8).…”
mentioning
confidence: 99%
“…The first group, 47 apparently healthy control subjects who were normoglycemic in the fasting condition, contained spouses of patients with MODY and volunteers from the medical personnel of the Department of Metabolic Diseases. The second group included 43 patients with type 2 diabetes diagnosed at age Ն35 years for whom no insulin therapy was used for at least 2 years after diagnosis, ascertained as previously described (13). The same exclusion criteria were used as for the MODY group.…”
mentioning
confidence: 99%